DEVELOPMENT OF A SOLID DOSAGE FORM WITH ADSORPTION ACTIVITY - M. V. Chirkova; D. K. Gulyaev; M. P. Chugunova; V. D. Belonogova (Фармация и фармакология (Пятигорск))
Enterosorbents are produced in various dosage forms – powders, tablets, pastes, etc., some of them are also manufactured in the form of capsules. A water-soluble polysaccharide complex (WSPC) manifesting a pronounced adsorption activity, which determines the prospects for the development of dosage forms of sorbents, was obtained from the cones of European Spruce (Picea abies).The aim of the work is to develop a solid dosage form with an adsorption activity based on a water-soluble polysaccharide complex from the cones of European Spruce (Picea abies).Materials and methods. The samples of European Spruce (Picea abies) cones were collected on the territory of Ilyinsky district of the Perm Krai and used as plant raw materials. A water-soluble polysaccharide complex was obtained from the raw materials. In order to improve the technological properties of the substance, (WSPC) granulates were obtained. The granulates were hand-made by wet granulation. The adsorption activity of the obtained granules was determined by the ability to bind methylene blue.Results. As a result of the experiment it has been established, that the WSPC substance of European Spruce (Picea abies) cones needs to be improved in its technological properties. Granulation of the substance led to an improvement in technological properties and an increase in the adsorption activity in most of the selected compositions. It has also been shown that increased moisture content of granulate decreases its adsorption activity. A direct dependence of the adsorption activity on the concentration of the granulating liquid (with the exception of some granulates) has been revealed, but no significant effect of the size of the granulate particles on the manifestation of the adsorption effect has been reported. According to the results of the study, a dosage form “Capsules” has been proposed for the compositions that showed the best results of the adsorption activity, and their biopharmaceutical evaluation was carried out according to the disintegration test.Conclusion. Thus, a solid dosage form with an adsorption activity has been obtained. The study shows the prospects for further research on the preparation of the drug with an adsorption activity based on the water-soluble polysaccharide complex of European Spruce (Picea abies) cones.